2023
DOI: 10.2147/prbm.s416312
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evidence of the Arabic Version of Nomophobia Questionnaire Among Physical Education Students

Abstract: Purpose Nomophobia refers to a psychological state in which individuals experience anxiety or fear at the thought of being disconnected from their mobile phone. The Nomophobia Questionnaire was developed to assess dimensions of nomophobia among native English-speaking populations. The purpose of this study was to adapt and validate the Nomophobia Questionnaire in the Tunisian context based on Western Arabic dialects. Methods This cross-sectional design using a non-proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…Physical activity has been demonstrated to be consistently and inversely associated with distress indicators in university students (9,10) . A cross-sectional study based on data from the Spanish National Health Survey 2017 involving 4195 participants showed that physical activity levels were linked to depression, anxiety and other mental health problems in Spanish youth (11).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity has been demonstrated to be consistently and inversely associated with distress indicators in university students (9,10) . A cross-sectional study based on data from the Spanish National Health Survey 2017 involving 4195 participants showed that physical activity levels were linked to depression, anxiety and other mental health problems in Spanish youth (11).…”
Section: Introductionmentioning
confidence: 99%
“…This has hampered the efforts of scientists, medical professsionals and governments to communicate effectively about the virus. The stress and anxiety triggered by the pandemic can lead to overuse the internet for information and comfort, exacerbating social isolation issues [5,6]. As vaccination decisions are influenced not only by health considerations but also by psychological factors such as trust, perceived risks and online information [7] problematic internet use potentially contributes to the spread of misinformation and affects vaccine perceptions [8].…”
Section: Introductionmentioning
confidence: 99%